Low-Cost Technologies that can be Integrated into Medical Education in Emerging Areas - Ţoţa, Paul; Vaida, Mircea-Florin (Current Medical Imaging, 2022)
Background: The situation created by global emergencies, such as the current global pandemic [1], has led in many parts of the world to the cessation of clinical practice in hospitals for medical and nursing students, although in medical education the contact with the patient and the practical practice of various medical techniques and procedures by contact is necessary. However, in situations of biological risk, it is natural to avoid any possibility of exposure for students. Materials and Methods: The objective of this paper is to analyze the possibility of creating low cost, modular telepresence robots, adapted for medical clinical practice and capable of allowing practicing students to interact remotely with patients, communicate with them, monitor them, help them move, and also to be able to measure parameters such as temperature using thermal vision, pulse measurement or, the ability of the limbs to move. The robot consists of a mobile stretcher, with the possibility of moving both with wheels and with the help of legs, which allows the patient to move without human assistance in areas with obstacles. The method of achieving this goal refers to the realization of several modular applications and each to solve specific tasks, and finally to be interconnected in a telepresence robot that makes possible the remote interaction of practicing students with patients. Results: The research results emerge both from the prototypes made and from the simulations and the results of measuring certain vital parameters sent by the telepresence robot via the internet to the medical team. Conclusion: The idea of modular integration of several individual applications is feasible and offers the advantage of easily adapting to patients with various ailments and medical needs.
Keywords: practice